Thermal requirements of trichogramma pretiosum (Hymenoptera: Trichogrammatidae) lines in neoleucinodes elegantalis (lepidoptera: Crambidae) eggs - Coutinho, Cristiane Ramos; Souza, SUYANNE ARAÚJO DE [UNESP]; Pontes, Antônia Débora Dos Santos; Godoy, MAURICIO SEKIGUCHI DE; Pereira, Fabricio Fagundes; Pastori, Patrik Luiz (SAGE Publications, 2021)
This study aimed to evaluate the impact of temperature on the development of two lines of Trichogramma pretiosum (Hymenoptera: Trichogrammatidae), to determine the thermal requirements of this parasitoid wasp on Neoleucinodes elegantalis (Lepidoptera: Crambi-dae) eggs. The experiment was carried out with two lines (“Ubajara” and “Guaraciaba”, Ceará State) of T. pretiosum collected naturally parasitizing eggs of N. elegantalis in tomato (Solanum lycopersicum) fruits. In this experiment, 40 eggs of the host N. elegantalis and 4 females of the parasitoids were used, with exposure to parasitism for 24 hours at 25 ± 1 °C, relative humidity of 70 ± 10 %, and 12-h photophase. At the end of this period, females were removed and the tubes were transferred to incubators (RH = 70 ± 10 %; 12-h photophase), exposed to 15, 20, 25, 30, or 35 °C, until emergence of the following generation of the parasitoids. The percentage of emergence, sex ratio, the number of parasitoids that emerged per egg, and cycle duration were assessed. The experiments were set up in a completely randomized experimental design with 5 treatments (temperatures) and 12 replicates. ANOVA was conducted and the means were compared by Tukey test (P < 0.05). The base temperatures were 10.77 °C and 10.86 °C and the number of generations per year were 33.29 and 35.63 for “Ubajara” and “Guaraciaba”, respectively. The study showed that temperature changed the biological parameters, and cycle duration of the “Ubajara” and “Guaraciaba” lines decreased as temperature increased.
Requerimientos térmicos de las líneas de trichogramma pretiosum (Hymenoptera: trichogrammatidae) en huevos de neoleucinodes elegantalis (lepidoptera: crambidae)
Keywords: Base temperature; Biological parameters; Crambidae; Egg parasitoids; Neoleucinodes elegantalis; Tomato fruit borer; Trichogramma pretiosum; Trichogrammatidae